Effects of walnut intake on anthropometric characteristics: A systematic review and dose-response meta-analysis of randomized controlled trials. (May 2020) - Fang, Zhang; Dang, Minyan; Zhang, Wenzhi; Wang, Yuewen; Kord-Varkaneh, Hamed; Nazary-Vannani, Ali; O. Santos, Heitor; Tan, Shing Cheng; C.T. Clark, Cain; Zanghelini, Fernando; Borges do Nascimento, Israel Júnior; Yang, Yongmei
Highlights: Walnut consumption has no significant effect on body weight, BMI, WC, and fat mass. Walnut intake significantly reduced BW, BMI and WC based on walnut dosage, up to the dosage of 35 g/day. Abstract: Background & objective: Effects of walnut intake on anthropometric measurements have been inconsistent among clinical studies. Thus, we conducted a meta-analysis of randomized clinical trials (RCTs) to evaluate and quantify the effects of walnut intake on anthropometric characteristics. Methods: We carried out a systematic search of all available RCTs up to June 2019 in the following electronic databases: PubMed, Scopus, Web of Science and Google Scholar. Pooled weight mean difference (WMD) of the included studies was estimated using random-effects model. Results: A total of 27 articles were included in this meta-analysis, with walnuts dosage ranging from 15 to 108 g/d for 2 wk to 2 y. Overall, interventions with walnut intake did not alter waist circumference (WC) (WMD: -0.193 cm, 95 % CI: -1.03, 0.64, p = 0.651), body weight (BW) (0.083 kg, 95 % CI: -0.032, 0.198, p = 0.159), body mass index (BMI) (WMD: -0.40 kg/m, 2 95 % CI: -0.244, 0.164, p = 0.703), and fat mass (FM) (WMD: 0.28 %, 95 % CI: -0.49, 1.06, p = 0.476). Following dose-response evaluation, reduced BW (Coef.= -1.62, p = 0.001), BMI (Coef.= -1.24, p = 0.041) and WC (Coef.= -5.39, p = 0.038) were significantly observed through walnut intake up to 35 g/day. However, the number of studies can be limited as to the individual analysis of the measures through the dose-response fashion. Conclusions: Overall, results from this meta-analysis suggest that interventions with walnut intake does not alter BW, BMI, FM, and WC. To date, there is no discernible evidence to support walnut intake for improving anthropometric indicators of weight loss.